Pedagogical Effectiveness of GMRCE Learning Model in Strengthening Learning Attitude in Gas Laws - Uy, Edison (JPAIR Institutional Research, 2023)
Science education is plagued by challenges, with students complaining about the learning process and teachers expressing exhaustion among students. The study investigated the pedagogical effectiveness of the modified processes of Gamification, Modeling, Rewarding, Cognitive Teamwork, and Explicit Timing (GMRCE) Model in strengthening students’ learning attitude in Gas Laws among Grade 10 Science students at Pangdan National High School during the School Year 2022-2023. The study utilized a pretest-posttest, comparison-group true-experimental design, measuring conceptual understanding through a three-tier 15-item test and assessing mathematical skills through a four-item word problem test. Descriptive-correlational research is designed to analyze personal profiles, including age, sex, academic performance, attitude toward science, proficiency level, and acceptability. Results showed that students with positive attitudes toward science achieved favorable academic performance, and the GMRCE Learning Model effectively improved students’ learning attitude in Gas Laws, which was deemed moderately acceptable, indicating a high satisfaction rating. The study suggests that teachers should use strategic learning models to encourage active participation and improve academic performance. A replicated study involving a larger group of participants may be conducted in other schools, and a qualitative approach may be integrated to validate the findings.
Keywords: Science Education; pedagogical effectiveness; GMRCE learning model; learning attitude; gas laws; quantitative; Philippines